Rehabilitation and care after hip fracture: a cost-utility analysis of stepped-wedge cluster randomized trial - Jonas A. Ipsen; Jan Abel Olsen; Bjarke Viberg; Lars T. Pedersen; Inge H. Bruun; Eva Draborg (Medical Journals Sweden, 2024)
Objective: To estimate the effectiveness and costs of Rehabilitation for Life (RFL) compared with usual rehabilitation and care after hip fracture to determine which course offered the most value for money. Design: Cost-utility analysis. Patient: Community-dwelling patients aged 65+ after hip fracture. Method: 123 intervention and 122 control patients were included. Data was collected at 5 points from discharge to 1-year follow-up. Cost analysis included expenses to hospital, general practice, specialist services, medications, rehabilitation, home and informal care, transport, and waiting times. The primary outcome was the incremental cost per quality-adjusted life year (QALY). Results: The intervention group experienced a statistically significant mean QALY gain of 0.02 -compared with the control group. The intervention was more costly by €4,224, resulting in an incremental cost of €159,990 per QALY gained. Two municipalities had several patients in respite care, yielding an imbalance. A subanalysis excluding these patients demonstrated QALY gain at 0.03 and the cost difference of €2,586 was not statistically significant. Conclusion: The intervention demonstrated a slight improvement in effectiveness over the control but was costly. For patients not requiring respite care, the intervention effect was slightly higher, and the cost differences statistically insignificant. In total 91% received informal care and the economic contribution of informal care exceeded the municipal home care services.